Antihyperlipidemic bioactivity of Alpinia officinarum (Hance) Farw Zingiberaceae can be attributed to the coexistance of curcumin, polyphenolics, dietary fibers and phytosterols. Issue 5 (13th May 2015) - Lin, Li-Yun; Peng, Chiung-Chi; Yeh, Xian-Yü; Huang, Bor-Yü; Wang, Hui-Er; Chen, Kuan-Chou; Peng, Robert Y.
<x xml:space="preserve">Abstract</x> Rhizoma A. officinarum (Hance) Farw, synonymously is called rhizoma galangae or smaller galangal (hereafter abbreviated as AO).